Contemporary Quantitative Finance Essays in Honour of Eckhard Platen - Chiarella, Carl; Novikov, Alexander (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The contributors to this volume write a series of articles outlining contemporary advances in a number of key areas of mathematical finance such as, optimal control theory applied to finance, interest rate models, credit risk and credit derivatives, use of alternative stochastic processes, numerical solution of equations of mathematical finance, estimation of stochastic processes in finance. The list of authors includes many of the researchers who have made the major contributions to these various areas of mathematical finance. This volume addresses both researchers and professionals in financial institutions, as well as regulators working in the above mentioned fields.